Sensitivity of US air quality to mid-latitude cyclone frequency and implications of 1980–2006 climate change - E. M. Leibensperger; L. J. Mickley; D. J. Jacob (Atmospheric Chemistry and Physics, 2008)
We show that the frequency of summertime mid-latitude cyclones tracking across eastern North America at 40°–50° N (the southern climatological storm track) is a strong predictor of stagnation and ozone pollution days in the eastern US. The NCEP/NCAR Reanalysis, going back to 1948, shows a significant long-term decline in the number of summertime mid-latitude cyclones in that track starting in 1980 (−0.15 a−1). The more recent but shorter NCEP/DOE Reanalysis (1979–2006) shows similar interannual variability in cyclone frequency but no significant long-term trend. Analysis of NOAA daily weather maps for 1980–2006 supports the trend detected in the NCEP/NCAR Reanalysis 1. A GISS general circulation model (GCM) simulation including historical forcing by greenhouse gases reproduces this decreasing cyclone trend starting in 1980. Such a long-term decrease in mid-latitude cyclone frequency over the 1980–2006 period may have offset by half the ozone air quality gains in the northeastern US from reductions in anthropogenic emissions. We find that if mid-latitude cyclone frequency had not declined, the northeastern US would have been largely compliant with the ozone air quality standard by 2001. Mid-latitude cyclone frequency is expected to decrease further over the coming decades in response to greenhouse warming and this will necessitate deeper emission reductions to achieve a given air quality goal.